Ligninolytic enzymes from tropical endophytic Xylariaceae - Urairuj C. (2014)
This paper focuses on ligninolytic enzyme production by 581 endophytic Xylariaceae strains isolated from healthy tropical native plants of northern Thailand. Strain CMUX144 was found to be the best manganese independent peroxidase producer. The effect of pH, temperature, initial glucose concentration and ammonium tartrate concentration on enzyme production by this strain was investigated. An activity of 195 U/l was achieved after cultivation at the optimum condition for 6 days. Enzyme activity reached 292 U/l when the media was supplemented with veratryl alcohol. The decolourization of Poly R-478 at various C/N ratios in media was investigated. Biological decolourisation following 12 days of cultivation was higher than 91%.